2020
DOI: 10.30884/jogs/2020.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Which Countries Generate Kondratieff Waves in Global GDP Growth Rate Dynamics in the Contemporary World?

Abstract: It is shown that the Kondratieff wave dynamics in the growth rates of global GDP is generated now by the developing countries, while in the previous era the Kondratieff dynamics was generated primarily by the most economically developed countries of the First World. We re-visit the question of the presence of the Kondratieff waves in the world GDP dynamics. We find that, though in the post 1960 series they are quite visible at the global level, they are hardly visible in the GDP growth rates of the economicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Therewith, a slight phase shift can be observed for the frequency range corresponding to the long cycles (0.025-0.015) (Fig. 2(b), 3(b), 4(b)), which is an empirical confirmation of the synchronisation of the time series of GDP per capita in the most industrialised countries, which are the main generators of long waves in the economy [23].…”
Section: Resultssupporting
confidence: 58%
“…Therewith, a slight phase shift can be observed for the frequency range corresponding to the long cycles (0.025-0.015) (Fig. 2(b), 3(b), 4(b)), which is an empirical confirmation of the synchronisation of the time series of GDP per capita in the most industrialised countries, which are the main generators of long waves in the economy [23].…”
Section: Resultssupporting
confidence: 58%
“…Thus, (Baburin, 2019) researched the resilience of the economies of the Greater Baltic Region to the cycles` conditions, calculated the cycle duration of 5-7 years and indicated that the main factor of stability of a country is its specialization. In their works (Korotayev et al, 2020) studied Kondratiev's long waves based on growth rates of global GDP and concluded that it is the developing countries that are generating such waves during the given period. (Göbel & Araújo, 2020) went further.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Demography is one of the important factors of convergence (Korotayev et al 2015(Korotayev et al , 2020, as it can make essential contribution to economic growth and its speed. The specific attention of researchers to the relationship between demographic and economic dynamics dates back to Thomas Malthus (1978Malthus ( [1798).…”
Section: Introductionmentioning
confidence: 99%